The Relevance of the Islamic Worldview in the Development of the Islamic Religious Education Curriculum - Della Anjelia Saputri; Agus Wahyu Triatmo (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to examine the relevance of an Islamic worldview in the development of an Islamic Religious Education (PAI) curriculum. The background of this research is based on the challenges of modern education, which tends to be secular and has implications for the weakening integration of Islamic values in the learning process. This study uses a qualitative approach with a literature review. Data were obtained from various sources, such as books, journal articles, and the works of Islamic education figures, then analyzed using content analysis techniques. The results indicate that an Islamic worldview plays a strategic role as a philosophical foundation in the development of an Islamic Religious Education (PAI) curriculum, particularly in determining educational objectives, developing materials, selecting learning methods, and evaluating the system. The Islamic worldview, grounded in monotheism, is able to integrate cognitive, affective, and spiritual aspects in education. Thus, developing an Islamic worldview-based PAI curriculum is a solution for shaping students with Islamic character and personality amidst the challenges of modernity.